2002
DOI: 10.1055/s-2002-26706
|View full text |Cite
|
Sign up to set email alerts
|

Soluble LDL-Immune Complexes in Type 2 Diabetes and Vascular Disease

Abstract: The increased level of circulating LDL-ICs is a risk factor for the general population, including those with diabetes. Our results suggested the contribution of LDL-ICs to the development of atherosclerosis to probably be more significant than the direct contribution of oxLDLAb itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…It may be argued that totally conclusive data has not yet been published, but it should be recognized that several groups have reported data that support the association of LDL-IC with manifestations of atherosclerosis, such as coronary artery disease [72; 79; 80; 114], myocardial infarction [81], intima-media thickening [82], and diabetic nephropathy [83; 85]. There is a need for reliable and simple assays so that the predictive value of oxLDL can be adequately assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be argued that totally conclusive data has not yet been published, but it should be recognized that several groups have reported data that support the association of LDL-IC with manifestations of atherosclerosis, such as coronary artery disease [72; 79; 80; 114], myocardial infarction [81], intima-media thickening [82], and diabetic nephropathy [83; 85]. There is a need for reliable and simple assays so that the predictive value of oxLDL can be adequately assessed.…”
Section: Discussionmentioning
confidence: 99%
“…These authors purified oxLDL and the corresponding IgG antibodies from atheromatous lesions of humans and Watanabe hyperlipidemic rabbits, thus demonstrating that the ingredients necessary for the formation of LDL-IC are present in the damaged arterial wall. Several groups, including ours, have reported a significant correlation between soluble LDL-IC and the presence of clinical and/or laboratorial evidence of cardiovascular disease [71; 72; 77; 78; 79; 80]. Lefvert et al have reported association between circulating IC measured by non-specific assays and myocardial infarction in individuals with less that 45 yrs of age [81] and found, in a prospective study, that such IC were “a strong and independent risk factor for myocardial infarction” in 50-yr-old men [61].…”
Section: Pathogenicity Of Modified Ldl Antibodies In Humansmentioning
confidence: 97%
“…Orekhov and coworkers reported that the level of cholesterol in isolated circulating IC, which reflects the amount of LDL-IC in circulation, correlated with the severity of coronary atherosclerosis [43,44]. Turk et al reported that the concentrations of Apo-B in circulating IC was significantly higher in patients with coronary heart disease [45]. A prospective study involving 98 diabetic subjects recruited as part of the Pittsburgh EDIC study showed that LDL-IC and oxLDL antibodies, correlated with the development of coronary artery disease [CAD] over a period of seven years, but while the correlation with LDL-IC levels was direct, the correlation with oxLDL antibody levels was inverse [37,38].…”
Section: The Pathogenic Role Of Immune Complexes Formed By Oxldl and mentioning
confidence: 99%
“…Orekhov and co-workers reported that the level of cholesterol in isolated circulating IC, which reflects the amount of LDL-IC in circulation, correlated with the severity of coronary atherosclerosis (16). Turk et al reported that the concentrations of ApoB in isolated serum IC, another parameter reflective of the concentration of circulating LDL-IC, was significantly higher in patients with coronary heart disease (17). Finally, a prospective study involving diabetic subjects showed that LDL-IC correlated with the development of coronary artery disease over a period of 7 years (18,19).…”
Section: Introductionmentioning
confidence: 99%